A comparison of encryption tools for disk data storage from digital forensics point of view - Moia, Vitor Hugo Galhardo; Henriques, Marco Aurélio A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2016: Anais do XVI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2016.19299, 2016)
A closer look from a digital forensics point of view may help us to find and understand vulnerabilities in cryptographic tools to determine which ones are the safest and provide the best features. In this paper, we analyze different ways of using cryptography to protect data on hard drives, discuss some vulnerabilities and present particular features of disk encryption tools. Then we analyze the security of some tools according to a set of criteria and evaluate the level of expertise required to use them. We conclude that the encryption subject impacts the scope of tools' vulnerabilities and full disk encryption is the safest and easiest option. Moreover, we highlight some free and easy to use tools that can protect users data properly if basic precautions are taken.